ASSESSMENT OF CLINICAL AND GENETIC RISK FACTORS OF ARTERIAL HYPERTENSION IN PERSONS YOUNGER THAN 35 YEARS OLD - I. M. Chernova; M. M. Lukianov; S. E. Serdyuk; S. A. Boytsov (Российский кардиологический журнал, 2015)
Aim. To study the specifics of clinical and genetic risk factors, office and 24-hour BP measurements in patients with AH of younger age, who have or have not had an increase of BP in childhood or adolescence.Material and methods. Totally 54 patients with AH studied at the age of 18-35 y.o. (mean age 25,3±3,4), of those 27 patients had AH since their 18 years age, 27 patients with verified essential AH — since childhood and adolescence. The controls were 26 healthy volunteers (mean age 25,8±3,7). 24-hour monitoring (ABPM) was done with the "ABPM" equipment (Meditech, Hungary). Gene polymorphism was studied using PCR.Results. In AH patients of child- and adolescent age there was significantly more prevalent abdominal obesity comparing to the group of AH patients not having the anamnesis of BP increase in that age (55,6% and 25,3%, resp., p=0,002). MS in AH patients of child- and adolescent age was two times more prevalent comparing to the group not having BP increase in that age (51,8% and 25,9%, resp., p=0,05). In comparison of RMS genes polymorphism and endothelial NO-syntase in the group of patients not having BP increase during childhood and adolescence, the genotype T/M of AGTgene is more prevalent (51,8% and 20,8%, resp.), and in comparison with control group genotype d/d of gene ACE (29,6% and 8%, resp.) and genotype A/C gene AT1R (48,1% and 20%, resp.)Conclusion. In patients with AH since childhood and adolescence there is higher prevalence of abdominal obesity and metabolic syndrome, but in patients with AH not having hypertension since this age, genetic factor prevail that probably influence the forming and course of AH in these groups with AH.